Methods of evaluation the quality of teaching in higher education institutions - Irina V. Barannikova; Elena N. Shaforostova (Статистика и экономика)
Purpose of research. The article describes an approach to assessing the quality of education at universities. Innovative processes in higher education increase the requirements to the quality assurance system for bachelors, masters, specialists and postgraduates. Such a system includes not only educational processes, but also the results of the quality of education. This problem is relevant because the quality of students’ training influences the formation of professional competencies and the demand on the labor market directly. The aim of the study is to develop a methodology for assessing the quality of training for different groups of experts.Materials and methods. The method of quality assessment and the results of the study, based on the proposed pyramid model of quality assessment with the details of the components, included in its composition, and the designation of their values for evaluation are considered in the paper. A method of assessing the quality of education at universities, based on the criteria of quality of education, the method of expert evaluation, formalization and algorithmization of the process is proposed. The generalized assessment of the group of experts is formed on the basis of average values. Formalization of assessment begins with the fact that in the built pyramid of quality of training each criterion is assigned a variable that reflects its assessment. The indicator, which is characterized by the average values of experts' assessments, is an assessment of the quality of training. Setting the relationship between quantitative and qualitative value is carried out using the established quality scale, which is based on the Likert scale. For a clear understanding of how the conclusion about the degree of consistency of experts by Kendall method is formed, the situation is considered when experts are asked to rank the criteria by significance, that is, to assign a place in the rating for each criterion. The overall assessment of the quality of education can be obtained based on a questionnaire that should be conducted on a specific topic and for all participants in the educational process, followed by an analysis of the survey results. Each expert group is offered a list of questions on a specific topic. To solve this problem, we should use the method of expert assessments, which is part of the theory of decision-making and expert evaluation - the procedure for obtaining an assessment of the task based on the opinion of experts, followed by decision-making.Results. The interest of the employer in carrying out this study is to increase the effectiveness of the quality of training, the formation of professional competencies, as well as an objective comprehensive assessment of the quality of training. As a result of the study, the pyramid of criteria and the model of evaluation of the quality of education allow to determine the value that reflects the qualitative characteristics of the learning process in higher education.Conclusion. The introduction of this model will improve the quality of the educational process in the University, to prepare highly qualified specialists in demand in the labor market, meet the needs of socio-economic development of modern society.